The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/jech-2019-213724
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery is associated with higher risk of overweight in the offspring: within-family analysis in the SUN cohort

Abstract: BackgroundMost studies assessing the association between caesarean delivery (CD) and childhood overweight/obesity have failed to account for important confounders, such as maternal prepregnancy body mass index (BMI) or the indication of the CD. Furthermore, within-family analyses have reported contradictory results. We aimed at evaluating the association between CD and offspring’s risk of overweight/obesity while adjusting for important confounders and accounting for correlations between siblings.MethodsWomen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Table 1: Main characteristics of studies included in the systematic review and meta-analysis on birth by Cesarean Section (CS) and offspring overweight/obesity. In our selection, 9 studies [29,30,31,32,33,34,35,36,37] have prospective study design and two studies have retrospective study design [38,39]. Two studies reported subtype of CS (Elective CS and Non elective CS) [29,39], four studies investigated the association of CS with overweight and obesity [29,33,37,39], one the association of CS with overweight [35] and six the association of CS with obesity [30,31,32,34,36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1: Main characteristics of studies included in the systematic review and meta-analysis on birth by Cesarean Section (CS) and offspring overweight/obesity. In our selection, 9 studies [29,30,31,32,33,34,35,36,37] have prospective study design and two studies have retrospective study design [38,39]. Two studies reported subtype of CS (Elective CS and Non elective CS) [29,39], four studies investigated the association of CS with overweight and obesity [29,33,37,39], one the association of CS with overweight [35] and six the association of CS with obesity [30,31,32,34,36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In our selection, 9 studies [29,30,31,32,33,34,35,36,37] have prospective study design and two studies have retrospective study design [38,39]. Two studies reported subtype of CS (Elective CS and Non elective CS) [29,39], four studies investigated the association of CS with overweight and obesity [29,33,37,39], one the association of CS with overweight [35] and six the association of CS with obesity [30,31,32,34,36,38]. Four studies were conducted in Europe (in particular, two in Denmark [35,39], one in Spain [37], one in Sweden [29]), 3 studies in USA [31,34,36], 2 studies in south America (Brazil) [30,32], one in Australia [33]and the remaining one in Africa (South Africa) [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations